THE FINANCING OF START UPS: A Survey on the Current State and Challenges in Finland - Veijalainen, Remi (My University, 2016)
Prior studies have highlighted the problematic state start ups find themselves in, while acquiring financing. Many of them experience issues while acquiring funding for their business, due to their lacking track record, proof for viability of the business model and lack of suitable investors. While prior studies have examined the financing of small businesses, little research has been conducted with regard to start ups. The intent of this study is to examine the capital acquisition decisions start ups make and the issues they may face in the process. This study also aims to examine whether certain entrepreneurial or business characteristics affect the outcome of financial negotiations, as well as their capital structure. In analyzing the data gathered through the online survey, this study will employ Spearman’s rank correlation coefficient and logistic ordinal regression. The findings of this study largely differ from prior research with regard to financing sources, difficulties in accessing capital and capital structure. The most important sources of external finance for the start ups in the sample of this survey were angel investors and governmental institutions for equity and financial, as well as governmental institutions for debt. This study finds that having an audited financial statement, intellectual property rights and having received external equity investments best predict the capital structure of a start up. Businesses with no external equity investments, were likely to have lower levels of all other capital classes.
Keywords: Start up; Capital Structure; Financing; Issues; Finland; Survey; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|